Comparative Study between Angiosome Directed Therapy and non Angiosome Therapy in Treatment of lower limb ischemia - Waleed Al baz; Hossam Abou Alenin; Mohammed Abd Al Mawala; Abdelhalim abdelhalim (Egyptian Journal of Medical Research, 2020)
Revascularization of the source artery to the angiosome result in better wound healing and limb salvage rates in comparison to failure of its revascularization as in our study showed that 90% better healing in directed Angiosome concept  and 20% in the which Angiosome concept not applied  direct revascularization  of arteries supplying the target angiosome (wound area) resulting in less complication and no further debridement is needed as in our study only  10% need post operative debridement in comparison to 80%  in the other group where Angiosome therapy couldn’t be applied